2021
DOI: 10.1021/jacs.1c07614
|View full text |Cite
|
Sign up to set email alerts
|

The Power of the Proton: From Superacidic Media to Superelectrophile Catalysis

Abstract: Superacidic media became famous in connection with carbocations. Yet not all reactive intermediates can be generated, characterized, and eventually isolated from these Brønsted acid/Lewis acid cocktails. The counteranion, that is the conjugate base, in these systems is often too nucleophilic and/or engages in redox chemistry with the newly formed cation. The Brønsted acidity, especially superacidity, is in fact often not even crucial unless protonation of extremely weak bases needs to be achieved. Instead, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 194 publications
(481 reference statements)
0
35
0
2
Order By: Relevance
“…The found reaction performance as a function of the nucleofuge (allyl ≈ Ph > H ≫ Me) is in accordance with the generally observed ease of Si−Nu bond protolysis. 14,19 Variation of the leaving group X in the alkyl halide under the optimized conditions for X = Br (entry 12) revealed that the method is not limited to alkyl bromides and all other alkyl halides also participate in the reaction (entries 17−19). A competition experiment demonstrated the selective conversion of alkyl fluoride 1a in the presence of alkyl bromide 1c.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The found reaction performance as a function of the nucleofuge (allyl ≈ Ph > H ≫ Me) is in accordance with the generally observed ease of Si−Nu bond protolysis. 14,19 Variation of the leaving group X in the alkyl halide under the optimized conditions for X = Br (entry 12) revealed that the method is not limited to alkyl bromides and all other alkyl halides also participate in the reaction (entries 17−19). A competition experiment demonstrated the selective conversion of alkyl fluoride 1a in the presence of alkyl bromide 1c.…”
Section: Resultsmentioning
confidence: 99%
“…The allylsilane 6g performed equally well as phenylsilane 6a (entry 15), whereas tetramethylsilane ( 6h ) was less efficient (entry 16). Although Me 4 Si is known to undergo protolysis in the presence of strong acids, this is an elusive example where this fully alkylated silane is intimately involved in a catalytic process. The found reaction performance as a function of the nucleofuge (allyl ≈ Ph > H ≫ Me) is in accordance with the generally observed ease of Si–Nu bond protolysis. , Variation of the leaving group X in the alkyl halide under the optimized conditions for X = Br (entry 12) revealed that the method is not limited to alkyl bromides and all other alkyl halides also participate in the reaction (entries 17–19).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of H-D exchange was analyzed via 1 H, 13 C, or 19 F 46 NMR spectroscopy (see ESI † for details). The mechanism of the H/D exchange likely involves the generation of superacidic protonated arenes in situ, 47 which should enable rapid H/D exchange via H + /D + shuttling (Fig. S4 †).…”
Section: Theoretical Ha Analysismentioning
confidence: 99%
“…47,48 The product of addition of either Et 3 Si + or F 6 Tr + to a neutral arene can be alternatively viewed as a protonated arene. 47 It is also possible that analogous cations are accessed via reactions involving the minor components of the mixture. The Oestreich group recently examined this type of H/D exchange catalysis in greater detail.…”
Section: Theoretical Ha Analysismentioning
confidence: 99%